2013
DOI: 10.1186/1472-6882-13-196
|View full text |Cite
|
Sign up to set email alerts
|

Spermicidal and anti-Trichomonas vaginalis activity of Brazilian Sapindus saponaria

Abstract: BackgroundSapindus saponaria is used traditionally for curing ulcers, external wounds and inflammations. The spermicidal and anti-Trichomonas activity of S. saponaria and its effect on Lactobacillus acidophilus were evaluated.MethodsWater-ethanol (WE) and butanolic (BE) extracts, as well as a purified sample of saponins (SP) from S. saponaria were tested for spermicidal and anti-Trichomonas activity and for their effect on L. acidophilus.ResultsWE, BE and SP immobilized spermatozoa at a minimum effective conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…It is used traditionally to cure ulcers, external wounds and inflammation. It was revealed that complimentary in vivo studies of Sapindus saponaria L. seeds should be made for establish the use as a viginal spermicidal, particularly in Brazil and Latin America [21]. Similar results were obtained in the aqueous extract of Sapindus trifoliatus L seeds.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…It is used traditionally to cure ulcers, external wounds and inflammation. It was revealed that complimentary in vivo studies of Sapindus saponaria L. seeds should be made for establish the use as a viginal spermicidal, particularly in Brazil and Latin America [21]. Similar results were obtained in the aqueous extract of Sapindus trifoliatus L seeds.…”
Section: Resultsmentioning
confidence: 53%
“…The root of M. oleifera were shown to possess antifertility, antiinflammatory and act as a cardiac or circulatory tonic, used as an abortifacient, treating kidney pain [20]. In vitro studies on Sapindus saponaria proved that it has viginal spermicidal activity [21]. Aqueous stem bark extract of Riccinus communis L showed dose dependent loss of sperm motility by influencing the morphological deformation of spermatozoa [22].…”
Section: Indo Global Journal Of Pharmaceutical Sciences Issn 2249-102mentioning
confidence: 99%
“…All samples induced erythrocyte lysis and release of LDH. An evaluation by Damke, Tsuzuki [28] of purified saponins of the medicinal plant of Sapindus saponaria, used traditionally to cure ulcers, external wounds, and inflammation revealed their inhibitory potency against T. vaginalis with an MIC value of 0.156 mg/ mL for nonclinical strains and 0.078 mg/mL for a clinical strain. Jain, Kumar [113] reported on a related study on the potential value of Sapindus saponaria trichomonocidal saponins for prophylactic contraception.…”
Section: Saponinsmentioning
confidence: 99%
“…Soapberry (Sapindus saponaria) is a native plant of Brazil [54], a medium size tree distributed all over the tropics and produce a large amount of small fruits yearly [54][55][56]. In America, Brazil and India, the fruits are traditionally used to manufacture soap [57,58] and as a clothing detergent [53,54]. Soapberry contains saponins in various parts [57].…”
Section: Documented Plant Sources Of Saponinmentioning
confidence: 99%